Quantitative Analysis of SARS-CoV-2 Serological Responses Post Three Doses of Immunization and Prior to Breakthrough COVID-19 Infections - Kathryn Macrae; Catherine Yuqing Gong; Prameet Sheth; Jorge Martinez-Cajas; Yanping Gong (Vaccines, 2022)
Background: Vaccine mediated SARS-CoV-2 antibody responses should be carefully evaluated. With regular follow-up in healthy individuals, we aimed to determine SARS-CoV-2 serological responses post three doses of immunization and prior to breakthrough infections in the Canadian population. Methods: In a prospective cohort study, we enrolled 140 healthy participants post COVID-19 vaccination in Kingston, Ontario, Canada. IgG antibodies against the SARS-CoV-2 spike receptor–binding domain were quantified by immunoassay post three doses of immunization. With COVID-19 rapid antigen test, polymerase chain reaction, and whole genome sequencing, 27 breakthrough infections were identified. Results: Following SARS-CoV-2 vaccine (including BNT162b2, AZD1222, and mRNA-1273), the median serum anti-spike protein antibody level was 143.6 BAU/mL (binding antibody unit, interquartile range 79.0–266.6) post the first dose of immunization, 1046.4 BAU/mL (423.9–1738.2) post the second dose, and 1604.7 BAU/mL (700.1–3764.0) post the third dose. Observed differences were significant (p ≤ 0.001). The median antibody level of 1604.7 BAU/mL post third dose is 45.6 times that of the seroconversion level (35.2 BAU/mL). This indicates that most vaccines approved are effective in producing robust antibody responses. In seven breakthrough cases characterized by whole genome sequencing, prior to infection, antibody concentrations of breakthrough cases were at 3249.4 (Delta), 2748.4 (Delta), 4893.9 (Omicron), 209.1 (Omicron), and 231.5 (Omicron), 725.7 (Omicron), and 2346.6 (Omicron) BAU/mL. Compared with the average antibody concentration of 2057.7 BAU/mL (58 times that of the seroconversion concentration) from above seven cases, 37.2% of triple vaccinated, 19.0% of double vaccinated, and 1.5% single dosed individuals have higher SARS-CoV-2 antibody levels. Conclusions: Most vaccines are effective in producing robust antibody responses when more than one dose is given, and the more doses the higher the serological response. Likely due to the highly contagious nature of SARS-CoV-2 variants, a significant number of participants have SARS-CoV-2 antibody responses lower than the average antibody concentration prior to the known breakthrough infections. Additional vaccination is likely required to ensure immunity against infection by SARS-CoV-2.